"Nahḍa" Epistolography: al-Shartūnī’s "al-Shihāb" and the Western Art of Letter-Writing - Patel, Abdulrazzak (Journal of Arabic and Islamic Studies, 2017)
Letter-writing represents one of the most important modes of communication in Islamic and Western societies. Arabic manuals on epistolography and collections of model letters abound throughout the medieval period and continued to be written right up to modern times. The research to date, however, has tended to focus on works of the pre-modern periods which rooted in the Islamic tradition cater primarily for a Muslim audience. Little is known about manuals produced in the Arab nahḍa and it is not clear what factors might have influenced them. Moving into the largely uncharted territory of nahḍa letter-writing manuals, this article takes a detailed look at al-Shartūnī’s manual on epistolary theory and model letters, al-Shihāb al-thāqib. An analysis of this work reveals it as a significant attempt by al-Shartūnī to appropriate elements of the Western ars dictaminis (the art of letter-writing) into his manual for the benefit of an Arab-Christian audience in the nahḍa.